2022
DOI: 10.3389/fnins.2022.855470
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intra- and Inter-Network Functional Connectivity in Patients With Crohn’s Disease: An Independent Component Analysis-Based Resting-State Functional Magnetic Resonance Imaging Study

Abstract: BackgroundMany studies have reported changes in the structure and function of several brain areas in patients with Crohn’s disease (CD). However, little is known about whether the possible functional connectivity of resting-state networks (RSNs) is altered in CD patients.PurposeAim to investigate the intra- and inter-network alterations between related RSNs in patients with CD and the potential relationships between altered neuroimaging and CD clinical indices.Materials and MethodsIn this study, 20 CD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Our finding of alterations in rs-FC in the DMN has been widely reported in CD literature in remission and active disease ( Thomann et al, 2017 , 2021 ; Bao et al, 2018 ; Liu et al, 2018 ; Hou et al, 2019 ; Kornelsen et al, 2020 ; Li et al, 2022 ; Goodyear et al, 2023 ). We show reduced rs-FC in the DMN in the parahippocampal gyrus (visuospatial processing and episodic memory) and cerebellum in active CD participants compared with HCs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our finding of alterations in rs-FC in the DMN has been widely reported in CD literature in remission and active disease ( Thomann et al, 2017 , 2021 ; Bao et al, 2018 ; Liu et al, 2018 ; Hou et al, 2019 ; Kornelsen et al, 2020 ; Li et al, 2022 ; Goodyear et al, 2023 ). We show reduced rs-FC in the DMN in the parahippocampal gyrus (visuospatial processing and episodic memory) and cerebellum in active CD participants compared with HCs.…”
Section: Discussionsupporting
confidence: 86%
“…We show that greater disease duration was associated with greater rs-FC in the middle temporal gyrus (language and semantic memory processing) and planum temporale (auditory perception and attention) in the visual anterior RSN (IC2). Altered functional connectivity in regions in the visual network has been reported before ( Li et al, 2022 ), where reduced rs-FC in the left calcarine was associated with greater disease duration. We postulate that disease duration is one of the variables that to an extent affect disease burden which may be related to the changes seen in visual network due to the increased chronic exposure of the CNS to symptom and chronic inflammatory stimuli.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Another study found increased FC between the frontoparietal (FP) network and the salience network (SN), and decreased FC between regions within the DMN ( Kornelsen et al, 2020 ). Li et al (2022) explored the abnormal FC of intra- and inter-brain networks in CD patients, and found increased FC of the language network with the left middle temporal gyrus and decreased FC of the prime visual network with the left calcarine. Agostini et al (2023) reported increased connectivity within the left FP network in inactive CD patients compared to active CD patients, decreased connectivity in the motor network in the active CD group compared to the HC group, and reduced connectivity in the motor network and in the language network in active CD patients compared to HCs.…”
Section: Resultsmentioning
confidence: 99%